1994
DOI: 10.1182/blood.v84.7.2269.2269
|View full text |Cite
|
Sign up to set email alerts
|

Primary tumor cells of myeloma patients induce interleukin-6 secretion in long-term bone marrow cultures

Abstract: Long-term bone marrow cultures (LTBMC) from patients with multiple myeloma (MM) and normal donors were analyzed for immunophenotype and cytokine production. Both LTBMC adherent cells from myeloma and normal donor origin expressed CD10, CD13, the adhesion molecules CD44, CD54, vascular cell adhesion molecule 1, very late antigen 2 (VLA-2), and VLA- 5, and were positive for extracellular matrix components fibronectin, laminin, and collagen types 3 and 4. LTBMC from myeloma patients and normal donors spontaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(48 citation statements)
references
References 42 publications
1
47
0
Order By: Relevance
“…The induction of IL-6 in BMSCs from myeloma patients and normal donors by myeloma tumor cell lines has already been described by other authors [ 28 ]. It has been found that BMSCs of MM patients produce more IL-6 than those of healthy controls.…”
Section: Discussionmentioning
confidence: 55%
“…The induction of IL-6 in BMSCs from myeloma patients and normal donors by myeloma tumor cell lines has already been described by other authors [ 28 ]. It has been found that BMSCs of MM patients produce more IL-6 than those of healthy controls.…”
Section: Discussionmentioning
confidence: 55%
“…The bone marrow microenvironment promotes MM proliferation and growth via the secretion of IL-6. IL-6 is a major growth factor and antiapoptotic cytokine for MM cells [ 32 ]; the importance of IL-6 as an autocrine growth factor for MM cells is widely accepted [ 24 ]. In the current experiment, aloperine overcame the proliferative effects of IL-6, IGF-I, and BMSCs, suggesting that aloperine could be efficacious in treating MM.…”
Section: Discussionmentioning
confidence: 99%
“…The purity of the MM cells was confirmed to be >90% via flow cytometric analysis using an anti-CD138 antibody (Miltenyi). CD138-negative mononuclear cells were also used to establish long-term BMSC cultures, as described previously [ 24 ]. BMSCs were obtained from MM patients and used between the third and fifth passages for all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, these cell lines have kept the major characteristic of primary myeloma cells whose survival is strictly dependent on the addition of exogenous IL-6 (Klein et al, 1989;Gu et al, 2000). In patients with multiple myelome (MM), IL-6 is largely produced by bone marrow stromal cells, indicating a paracrine stimulation of tumor cell survival by their environment (Portier et al, 1991;Uchiyama et al, 1993;Lokhorst et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Human myeloma cells (HMCL) survive and proliferate in close contact with bone marrow stromal cells (Klein et al, 1989;Uchiyama et al, 1993;Lokhorst et al, 1994). Interleukin-6 (IL-6) is one of the survival factors delivered by stromal cells.…”
Section: Introductionmentioning
confidence: 99%